The dual regulatory effects of intestinal microorganisms and their metabolites in gouty arthritis pathogenesis: a balance between promotion and inhibition - Qi, Peng; Li, Longcan; Zhang, Jianrong; Ren, Ling; Xie, Xingwen (Frontiers in Immunology, 2025)
Gout is an arthritis characterized by the deposition of urate crystals, often accompanied by robust inflammatory responses. The gut microbiome profoundly influences gout pathogenesis, progression, and management by affecting uric acid metabolism, immune responses, and intestinal barrier function. Studies reveal that gut microorganisms exert a dual role in gout development. Gout patients typically exhibit increased harmful bacterial abundance and reduced beneficial species. Harmful bacteria and associated metabolites can influence systemic uric acid levels by regulating excretion and synthesis, thereby promoting gout manifestations. Conversely, beneficial bacteria interact with the host immune system to inhibit inflammation and modulate the inflammatory state of joints. Furthermore, the gut microbiome can significantly impact gout treatment efficacy through its influence on drug metabolism and absorption. Research highlighting the gut-joint-inflammation axis offers novel therapeutic strategies for gout, suggesting that future approaches may involve microbiome modulation to enhance clinical outcomes.